Evaluasi Persiapan Perpustakaan Stikes 'Aisyiyah Yogyakarta Dalam Membangun Perpustakaan Digital - Irkhamiyati Irkhamiyati (Berkala Ilmu Perpustakaan dan Informasi, 2017)
The development of information technology becomes necessary to serve library users, particularly to  develop digital libraries. The aim of this study is to examine the preparation of the library of STIKES Aisyiyah Yogyakarta to build digital libraries, users and policy makers expectations, and ways  to solve the challenges. Using qualitative descriptive approachand purposive sampling, data collection technique was conducted by using observations, in-depth inteviews, and documentations. The data was analysed by using validity of test data. Evaluation of the results was framed by  the works  of Ian H. Witten- David Bainbridge and Lucy A. Tedd. The results showed that most of the components were already prepared in the library of STIKES Aisyiyah Yogyakarta’ s  in developinga digital library, however, but there were several components that need to  be prepared better, such as  human resources and time management. Several efforts have been and will be made to address those concerns to avoid  failure to build a digital library. The idea to outsource should be considered. . The addition of experts from outside of the library as part of the team are needed to further strengthen the digital library development.The author suggested that the library staff continue to increase knowledge about the digital libraries, to overcome the technical obstacles emerged.